PREVALENCE OF INVALIDITIES CONNECTED WITH CHILD EYE DISEASES - L.V. Nefedovskaya; R.N. Terletskaya ("Paediatrician" Publishers LLC, 2008)
Invalidity conditioned by diseases of the eye and its accessory apparatus constitutes approximately 1% of the overall structure of child invalidity in Russia. Maximum figures are registered in boys aged 10-14. The figures of child eye invalidity in federal regions (FR) are close to overall Russian figures. The most diresituation is registered in Privolzhky and south FO.Key words: children, invalidity, eye diseases, regional specifics.